2013
DOI: 10.1177/2050640613476501
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a standard fully covered stent with a super‐thick silicone‐covered stent for the treatment of refractory esophageal benign strictures: A prospective multicenter study

Abstract: Background: Some esophageal strictures resist endoscopic treatments. There is a need for new treatments, such as specifically designed stents. Objective: Our study sought to compare the results achieved with a standard, fully covered metallic stent (FCMS) and those achieved using a stent designed specifically for benign strictures (BS-FCMS). Patients and methods: The study used a prospective, multicenter, controlled design, with patients recruited from tertiary referral centers. Patients with refractory esopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Nevertheless, the poor results of covered stents in the treatment of benign oesophageal strictures of any kind, and the absence of any anti‐proliferative or anti‐inflammatory/anti‐fibrotic effect of the stents—indeed, with a possible pro‐inflammatory action—make stenting an unlikely candidate for the title of best prophylactic method. Thus, the results from Weng et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the poor results of covered stents in the treatment of benign oesophageal strictures of any kind, and the absence of any anti‐proliferative or anti‐inflammatory/anti‐fibrotic effect of the stents—indeed, with a possible pro‐inflammatory action—make stenting an unlikely candidate for the title of best prophylactic method. Thus, the results from Weng et al .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, only patients who experienced stent migration developed a stricture. 114 Nevertheless, the poor results of covered stents in the treatment of benign oesophageal strictures of any kind, 115 and the absence of any anti-proliferative or antiinflammatory/anti-fibrotic effect of the stents-indeed, with a possible pro-inflammatory action-make stenting an unlikely candidate for the title of best prophylactic method. Thus, the results from Weng et al need to be confirmed in larger studies before oesophageal stent placement can be considered as a valid option to prevent stricture development.…”
Section: Mechanical Approachmentioning
confidence: 99%
“…As for malignant dysphagia, but without formal FDA approval, fcSEMS have also been investigated in clinical trials treating RBES [ 46 48 ]. The clinical success rates of fcSEMS are likely to be comparable and not significantly different from SEPS and BDS [ 42 ], although this has never been investigated in head-to-head RCTs.…”
Section: Utilization and Limitations Of Esophageal Stentsmentioning
confidence: 99%
“…The stent then becomes completely embedded into the esophageal mucosa by the 4th–6th week. Massive granulation tissue can result in partial esophageal stricture by the 8th week or later [ 16 ]. Various methods have been introduced to successfully remove stent in patients with embedded stent, such as stent-in-stent (SIS) technique, argon plasma coagulation, and the overtube technique [ 4 ].…”
Section: Discussionmentioning
confidence: 99%